Combination of intralesional verapamil and oral antioxidants for Peyronie's disease: a prospective, randomised controlled study. (11th October 2013) - Favilla, V.; Russo, G. I.; Privitera, S.; Castelli, T.; Madonia, M.; La Vignera, S.; Condorelli, R.; Calogero, A. E.; Farina, F. P.; Cimino, S.; Morgia, G.
Summary The aim of this study was to evaluate the efficacy of the association of intralesional verapamil (ILV) injection with oral antioxidants compared with ILV monotherapy in patients with early onset of Peyronie's disease (PD) at 12‐week follow‐up. Group A (n = 52) received ILV 10 mg weekly for 12 weeks, while group B (n = 53) received ILV 10 mg weekly for 12 weeks + antioxidants orally one tablet once a day for 3 months. The main efficacy outcomes were the change in plaque size (PS), penile curvature (PC), visual analogue score (VAS), IIEF‐15 and IIEF‐15 subdomains. Both groups showed significant improvement from baseline to week 12 relative to PS and PC, while group B also in IIEF‐15 score (mean difference: 5.51, P < 0.01) and VAS (mean difference: −2.71, P < 0.01). No significant differences were observed between both groups in PS and PC. Finally, both groups showed significant increase in orgasmic function (IIEF‐OF) and overall satisfaction (IIEF‐OS), while group B showed significant improvement also in intercourse satisfaction (IIEF‐IS). Significant differences were found relative to IIEF‐OF, IIEF‐IS, IIEF‐OS and VAS scores in the group B compared with group A. Patients affected by PD may benefit from combination treatment with ILV and oral antioxidants thanks to the improvement in IIEF‐OF, IIEF‐IS and IIEF‐OS at 12 weeks.